Over 10 years of variation in Mediterranean reef benthic communities. (20th June 2017) - Betti, Federico; Bavestrello, Giorgio; Bo, Marzia; Asnaghi, Valentina; Chiantore, Mariachiara; Bava, Simone; Cattaneo‐Vietti, Riccardo
Abstract: During the last several decades, the Mediterranean littoral shallow water benthic communities have suffered significant changes in their structure and taxa composition. Despite numerous studies conducted to characterize these changes at various levels, it has always been very difficult to disentangle the effects of natural factors from anthropic ones. The main purpose of this work was to evaluate possible changes, over a 10‐year scale, in diversity and abundance of the most representative species of the benthic communities considered to be primarily and potentially affected by natural stressors in a highly protected area. Sets of macro‐photographs were taken in 2002–2003 of three sites inside a small bay called Ca' dell'Oro, which is the "no entry—no take" zone of the Marine Protected Area of Portofino, in order to analyse the structure of the benthic communities at different depths over a short time scale. The same sampling was repeated 10 years later in 2013. In the 10‐year span, a significant change in the macroalgal coverage and composition was observed, while the overall richness and coverage of species remained almost unchanged. This process resulted in a significant reduction of the habitat complexity of the three‐dimensional algal components. Likewise, a remarkable change in terms of presence and abundance occurred among all zoobenthic components. The benthic communities seem to have suffered from detrimental effects probably caused by climatic events that have been occurring in recent years in the Ligurian Sea.